ANALISIS UNSUR INTRINSIK DAN EKSTRINSIK CERPEN MAI BARENTAIN DE- (MY VALENTINE DAY) KARYA ATODA TAKASHI 阿刀田高の短編「マイバレンタインデー」の内在的要素と 外在的要素を分析した - Khodijah, Siti (Japanese Literature, 2013)
Khodijah, Siti. “Unsur Intrinsik dan Ekstrinsik Cerpen Mai Barentain De- (My Valentine Day) Karya Atoda Takashi”. Thesis. Department of Japanese Studies Faculty of Humanities. Diponegoro University. The first advisor Drs. Yudiono KS, SU. The second advisor Yuliani Rahmah, S.Pd, M.Hum. My Valentine Day is a pop teen short story by Atoda Takashi. This short story tell us about Valentine day but with a mystery content, that’s the unique point of My Valentine Day. This story started when valentine day’s night, Kyoko main character a senior high school student bought a medicine for her mother. After that, Kyoko met an old women who sell a valentine’, because that old women look so poor, Kyoko bought that chocolate. The old women said that if Kyoko gave the chocolate for someone she love, that man will love her back. Kyoko didn’t believe it because Kyoko didn’t have a boyfriend. Finally, Kyoko sent that chocolate to a popular actor named K, at the night, Kyoko dreamed about K, in her dream, Kyoko and K was sit together at the beautiful garden. Many years later, Kyoko merried with a man, but K still single. Everytime he got a question about his single status, he always said that he looked a girl who sat down at the garden with him in his dream. The purpose of this study was to analyze the building blocks of the short story of “ My Valentine Day”. The analyzed elements were the theme, plot, character, setting, point of view, the message and cultural background. Keywords: Valentine Day, Short stories, Mystery, intrinsic and ekstrinsik elements.